Design of experiments to assess the effect of culture parameters on the osteogenic differentiation of human adipose stromal cells - Kuterbekov, Mirasbek; Machillot, Paul; Baillet, Francis; Jonas, Alain M.; Glinel, Karine; Picart, Catherine (Stem cell research & therapy, 2019)
Background Human adipose-derived stromal cells (hASCs) have been gaining increasing popularity in regenerative medicine thanks to their multipotency, ease of collection, and efficient culture. Similarly to other stromal cells, their function is particularly sensitive to the culture conditions, including the composition of the culture medium. Given the large number of parameters that can play a role in their specification, the rapid assessment would be beneficial to allow the optimization of their culture parameters. Method Herein we used the design of experiments (DOE) method to rapidly screen the influence and relevance of several culture parameters on the osteogenic differentiation of hASCs. Specifically, seven cell culture parameters were selected for this study based on a literature review. These parameters included the source of hASCs (the different providers having different methods for processing the cells prior to their external use), the source of serum (fetal bovine serum vs. human platelet lysate), and several soluble osteoinductive factors, including dexamethasone and a potent growth factor, the bone morphogenetic protein-9 (BMP-9). The expression of alkaline phosphatase was quantified as a readout for the osteogenic differentiation of hASCs. Results The DOE analysis enabled to classify the seven studied parameters according to their relative influence on the osteogenic differentiation of hASCs. Notably, the source of serum was found to have a major effect on the osteogenic differentiation of hASCs as well as their origin (different providers) and the presence of L-ascorbate-2-phosphate and BMP-9. Conclusion The DOE-based screening is a valuable approach for the classification of the impact of several cell culture parameters on the osteogenic differentiation of hASCs.